Inhibitory control and problem solving in early childhood: Exploring the burdens and benefits of high self‐control. Issue 3 (5th January 2022) - Hendry, Alexandra; Agyapong, Mary A.; D'Souza, Hana; Frick, Matilda A.; Portugal, Ana Maria; Konke, Linn Andersson; Cloke, Hamish; Bedford, Rachael; Smith, Tim J.; Karmiloff‐Smith, Annette; Jones, Emily J.H.; Charman, Tony; et al.
Abstract: Low inhibitory control (IC) is sometimes associated with enhanced problem‐solving amongst adults, yet for young children high IC is primarily framed as inherently better than low IC. Here, we explore associations between IC and performance on a novel problem‐solving task, amongst 102 English 2‐ and 3‐year‐olds (Study 1) and 84 Swedish children, seen at 18‐months and 4‐years (Study 2). Generativity during problem‐solving was negatively associated with IC, as measured by prohibition‐compliance (Study 1, both ages, Study 2 longitudinally from 18‐months). High parent‐reported IC was associated with poorer overall problem‐solving success, and greater perseveration (Study 1, 3‐year‐olds only). Benefits of high parent‐reported IC on persistence could be accounted for by developmental level. No concurrent association was observed between problem‐solving performance and IC as measured with a Delay‐of‐Gratification task (Study 2, concurrent associations at 4‐years). We suggest that, for young children, high IC may confer burden on insight‐ and analytic‐aspects of problem‐solving.